(3eUMa TQjas ((3CMeO Hf CHj LdGd GdYTQi s)
(3ChdgG (B:s
(3ShQI GdaGJMI s
(3BNQgG (B:s
(3ShQI GdfGS s
(3HgG HYV GdRjGOGJ ai BNQgG hJedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcJH GdSeGhjIs